Analysis of Leadership and Managerial Functions on the Km. Sultan Hasanuddin as an Inter-Island Pioneer Ship in Makassar - Nurkhalis Nurkhalis; Muhammad Ridwan Arif; Sri Adrianti Muin (Scieclouds Publishing, 2026)
This study examines the effectiveness of leadership and managerial functions on KM Sultan Hasanuddin, an inter-island pioneer vessel operating in Eastern Indonesia. Maritime operations present unique challenges due to their high-risk, isolated, and hierarchical environment, making leadership a critical determinant of safety and performance. This research adopts a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving seven informants representing top, middle, and lower management levels on board. Data analysis followed the Miles and Huberman model, supported by triangulation techniques to ensure validity. The findings reveal that the captain applies a situational leadership approach by integrating transformational and transactional leadership styles within the Full Range Leadership Model (FRLM). Transformational elements are reflected in motivational and inclusive interactions that foster crew cohesion and reduce burnout, while transactional elements ensure strict adherence to standard operating procedures (SOPs), particularly in emergency and technical operations. The implementation of managerial functions (Planning, Organizing, Actuating, and Controlling) demonstrates strong organizational structure, clear task division, and systematic evaluation mechanisms, contributing to operational stability and zero-incident performance. Furthermore, organizational communication is characterized by open, participatory, and adaptive patterns, supported by both formal (HT communication) and informal channels, despite technical barriers such as signal limitations. This study concludes that effective leadership on board is achieved through adaptive leadership shifting, strong managerial integration, and resilient communication systems, which collectively enhance safety, efficiency, and crew well-being in maritime operations.